Platform Design of Auxiliary Converter for Metro Vehicle - LIU Qing; WANG Ming; WEI Zhouyan; ZHAO Qingliang (Kongzhi Yu Xinxi Jishu)
It introduced the technical parameters, main circuit, overall structure and characteristics of the auxiliary converter platform products for metro vehicles, and described the design method of auxiliary converter in performance improvement.